Charge transfer from an adsorbed ruthenium-based photosensitizer through an ultra-thin aluminium oxide layer and into a metallic substrate - Gibson, Andrew J.; Temperton, Robert H.; Handrup, Karsten; Weston, Matthew; Mayor, Louise Charlotte; O'Shea, James N. (American Institute of Physics, 2014)
The interaction of the dye molecule N3 (cis-bis(isothiocyanato)bis(2,2-bipyridyl-4,4′-dicarbo-xylato)-ruthenium(II)) with the ultra-thin oxide layer on a AlNi(110) substrate, has been studied using synchrotron radiation based photoelectron spectroscopy, resonant photoemission spectroscopy, and near edge X-ray absorption fine structure spectroscopy. Calibrated X-ray absorption and valence band spectra of the monolayer and multilayer coverages reveal that charge transfer is possible from the molecule to the AlNi(110) substrate via tunnelling through the ultra-thin oxide layer and into the conduction band edge of the substrate. This charge transfer mechanism is possible from the LUMO+2 and 3 in the excited state but not from the LUMO, therefore enabling core-hole clock analysis, which gives an upper limit of 6.0 ± 2.5 fs for the transfer time. This indicates that ultra-thin oxide layers are a viable material for use in dye-sensitized solar cells, which may lead to reduced recombination effects and improved efficiencies of future devices.